Exploring the molecular mechanisms of electron shuttling across the microbe/metal space - Paquete, Catarina M.; Fonseca, Bruno M.; Cruz, Davide R.; Pereira, Tiago M.; Pacheco, Isabel; Soares, Cláudio M.; Louro, Ricardo O. (Frontiers in Microbiology, 2014)
Dissimilatory metal reducing organisms play key roles in the biogeochemical cycle of metals as well as in the durability of submerged and buried metallic structures. The molecular mechanisms that support electron transfer across the microbe-metal interface in these organisms remain poorly explored. It is known that outer membrane proteins, in particular multiheme cytochromes, are essential for this type of metabolism, being responsible for direct and indirect, via electron shuttles, interaction with the insoluble electron acceptors. Soluble electron shuttles such as flavins, phenazines and humic acids are known to enhance extracellular electron transfer. In this work, this phenomenon was explored. All known outer membrane decaheme cytochromes from Shewanella oneidensis MR-1 with known metal terminal reductase activity and a undecaheme cytochrome from Shewanella sp. HRCR-6 were expressed and purified. Their interactions with soluble electron shuttles were studied using stopped-flow kinetics, NMR spectroscopy and molecular simulations. The results show that despite the structural similarities, expected from the available structural data and sequence homology, the detailed characteristics of their interactions with soluble electron shuttles are different. MtrC and OmcA appear to interact with a variety of different electron shuttles in the close vicinity of some of their hemes, and with affinities that are biologically relevant for the concentrations typical found in the medium for this type of compounds. All data support a view of a distant interaction between the hemes of MtrF and the electron shuttles. For UndA a clear structural characterization was achieved for the interaction with AQDS a humic acid analogue. These results provide guidance for future work of the manipulation of these proteins toward modulation of their role in metal attachment and reduction.